Cost-effectiveness of various tuberculosis control strategies in Thailand - Pojjana Hunchangsith (2018)
Objective: To evaluate the cost-effectiveness of different tuberculosis control strategies in Thailand. Methods: Different tuberculosis control strategies, which included health-worker, community-member, and family-member directly observed treatment (DOT) and a mobile phone "contact- reminder" system, were compared with self-administered treatment (SAT). Cost-effectiveness analysis was undertaken by using a decision tree model. Costs (2005 international dollars [I$]) were calculated on the basis of treatment periods and treatment outcomes. Health outcomes were estimated over the lifetime of smear-positive pulmonary tuberculosis patients in disability-adjusted life years (DALYs) averted on the basis of Thai evidence on the efficacy of the selected strategies. Results: Cost-effectiveness results indicate no preference for any strategy. The uncertainty ranges surrounding the health benefits were wide, including a sizeable probability that SAT could lead to more health gain than DOT strategies. The health gain for family-member DOT was 9400 DALYs (95% uncertainty interval -7200 to 25,000), for community-member DOT was 13,000 DALYs (95% uncertainty interval -21,000 to 37,000), and for health-worker DOT was 7900 DALYs (95% uncertainty interval -50,000 to 43,000). There were cost sa vings (from less multi-drug resistant tuberculosis treatment) associated with family-member DOT (-I$9 million [95% uncertainty interval -I$12 million to -I$5 million] ) because the trial treatment failure rate was significantly lower than that for SAT. The mobile phone reminder system was not cost-effective, because the mortality rate associated with it was much higher than that associated with other treatment strategies. Conclusions: Because of the large uncertainty intervals around health gain for DOT strategies, it remains inconclusive whether DOT strategies are more cost-effective than SAT. It is evident, however, that family-member DOT is a cost-saving intervention. © 2012 International Society for Pharmacoeconomics and Outcomes Research (ISPOR).